Decolonization of knowledge-production: critical turn in Romani studies - Dunajeva, Jekatyerina (Romano džaniben, 2023)
The text presents a body of literature in the field of Romani studies that adopts the broader emphases of postcolonialism and decolonization. In doing so, it focuses primarily on the circumstances of the emergence of the Critical Romani Studies movement and the journal of the same name. In this context, it touches on the broader questions of who produces knowledge about the Roma and in what ways.